Participation in Employer-sponsored Training in Canada’s Regions - He, Jingyi (Université d'Ottawa | University of Ottawa, 2009)
This paper uses data from the 2003 Canadian Adult Education and Training Survey to investigate wthether the effect of participation in employer-sponsored traiining in the form of work-related courses is the same, conditional on individual, job-related and